Combining GPS and space syntax analysis to improve understanding of visitor temporal–spatial behaviour: a case study of the Lion Grove in China. (18th May 2020) - Zhang, Tiantian; Lian, Zefeng; Xu, Yannan
ABSTRACT: Visitor tracking combined with space analysis has recently emerged as a method for understanding the relationship between visitor temporal–spatial behaviour and spatial features. In this study, 353 visitors were tracked using handheld GPS data loggers to enable calculation of visiting proportion, average time, and average speed in each space within the Lion Grove. Using ArcGIS to superimpose tracks and conduct a kernel density analysis, the popular and less-popular spaces were determined. The characteristics of the different spatial features were then analysed using Depthmap. The Spearman correlation was then employed to analyse the relationship between visitor temporal–spatial behaviour and the characteristic values of different spaces. The results demonstrate that walking accessibility decides the probability of a first-time visit, while the main factors attracting visitors to stay depends on the visual characteristics of the space, such as visual accessibility and visual permeability.